The Influence of Job Stress, Workaholism and Work Engagement on Job Satisfaction and Turnover Intention in the Garment Industry - Valusi Tri Wulandari; Gilang Pratama Hafidz (Lafadz Jaya Publisher, 2023)
The phenomenon of turnover intention in the garment industry is already rife. The high turnover intention will occur if the company does not realize a large number of jobs available while the resources are minimal. Then it can lead to job stress and workaholic behavior. This study aims to find out and reveal whether the factors of job stress, workaholism, work engagement, and job satisfaction have a significant effect on turnover intention among management employees in companies engaged in the garment industry in Indonesia. The population of this study was employees at companies engaged in the global brand garment industry (BONPRIX, C&A, H&M, etc.) in Jakarta, Bogor, Depok, Tangerang, and Bekasi. While the sample is part of the population who has worked in management for at least 1 year. This research is a quantitative research that collects data using the Non-Probability sampling method from July to August 2022 with a sample size of 165 people and uses the Structural Equation Model - Partial Least Square (SEM-PLS) data processing method. The result is that work engagement has an impact on increasing job satisfaction, workaholism can increase turnover intention, and job satisfaction can reduce turnover intention. Furthermore, work engagement can reduce the level of turnover intention and job stress can increase the turnover intention of management employees in companies engaged in the garment industry in Indonesia.